Mechanical properties of cellulose nanofibril papers and their bionanocomposites: A review - Mokhena, Teboho Clement; Sadiku, Emmanuel Rotimi; Mochane, Mokgaotsa Jonas; Ray, Suprakas Sinha; John, Maya Jacob; Mtibe, Asanda (Carbohydrate polymers, 2021)
Cellulose nanofibril (CNF) paper has various applications due to its unique advantages. Herein, we present the intrinsic mechanical properties of CNF papers, along with the preparation and properties of nanoparticle-reinforced CNF composite papers. The literature on CNF papers reveals a strong correlation between the intrafibrillar network structure and the resulting mechanical properties. This correlation is found to hold for all primary factors affecting mechanical properties, indicating that the performance of CNF materials depends directly on and can be tailored by controlling the intrafibrillar network of the system. The parameters that influence the mechanical properties of CNF papers were critically reviewed. Moreover, the effect on the mechanical properties by adding nanofillers to CNF papers to produce multifunctional composite products was discussed. We concluded this article with future perspectives and possible developments in CNFs and their bionanocomposite papers. •Mechanical properties of cellulose nanofibril papers are thoroughly discussed.•Primary factors influencing mechanical properties are elucidated.•Reinforcing cellulose nanofibril papers with various nanofillers to produce multifunctional composites.